German and Italian Users of Web-Accessed Genetic Data: Attitudes on Personal Utility and Personal Sharing Preferences. Results of a Comparative Survey (n=192) - Wöhlke, Sabine; Schaper, Manuel; Oliveri, Serena; Cutica, Ilaria; Spinella, Francesca; Pravettoni, Gabriella; Steinberger, Daniela; Schicktanz, Silke (Frontiers in Genetics, 2020)
Genetic information is increasingly provided outside of the traditional clinical setting, allowing users to access it directly. This development is possibly resulting in changing ethical and social challenges for users of predictive genetic tests. Little is known about the attitudes and experiences of users of web-accessed genetic information. This survey analyzes data from two European countries with regard to the utility of genetic information, the users’ ways of making use of and dealing with information, and their sharing behavior. Particular focus is given to ethical and social questions regarding the motivation to share personal genetic results with others. Social factors tested for are national background, gender, and marital, parental and educational status. This study will contribute to public discourse and offer ethical recommendations. The study will also serve to validate the developed questionnaire for use in population representative surveys.